Toward improved drought tolerance in bioenergy crops: QTL for carbon isotope composition and stomatal conductance in Populus. (3rd December 2013) - Viger, Maud; Rodriguez‐Acosta, Maricela; Rae, Anne M.; Morison, James I. L.; Taylor, Gail
Abstract: Dedicated non‐food bioenergy crops like poplar are needed as sustainable, low‐input feedstocks for renewable energy in a future drier climate, where they can be grown on marginal soils. Such plants should have a low water, carbon, and chemical footprint. Capturing natural variation in traits associated with water use efficiency (WUE) is the first step to developing trees that require less water and may be adapted to drier environments. We have assessed stomatal conductance ( g s ) and leaf carbon isotope composition (δ 13 C, an indirect indicator of leaf WUE) in two Populus species, P. deltoides and P. trichocarpa and their F2 progeny, grown in the United Kingdom and in Italy. Populus deltoides leaves showed lower δ 13 C than P. trichocarpa, suggesting a higher WUE in P. trichocarpa, although without drought preconditioning, g s of P. trichocarpa was less responsive to dehydration and abscisic acid treatment than P. deltoides, suggesting that leaf anatomy may also contribute to δ 13 C in Populus . Quantitative trait loci (QTL) were identified for δ 13 C on eight linkage groups (LG) and two QTL for g s . From these. QTL and differential gene expression in response to drought from microarray data, we focused on three hotspots and identified 23 novel candidate genes on LG VI, X, and XVI. We have begun to unravel the genetic basis of WUE in bioenergy Populus revealing important underpinning data for breeding and improvement in poplar genotypes for a future drier climate. Abstract : Dedicated non‐food bioenergy crops like poplar are needed as sustainable, low‐input feedstocks for renewable energy in a future drier climate, where they can be grown on marginal soils. We have assessed stomatal conductance ( g s ) and leaf carbon isotope composition (δ13C) in two Populus species, P. deltoides and P. trichocarpa and their F2 progeny, grown in the United Kingdom and in Italy. Quantitative trait loci (QTL) were identified for δ13C on eight linkage groups (LG) and two QTL for g s .